Vision Crisis and Change Management in a Rapidly Changing World - Masoud, Najeb; Abu Sabha, Suleiman (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
The purpose of this study is to investigate and discuss current literature on crisis management within organisational settings. The key characteristic of a crisis is that you cannot control it that’s why they call it crisis “management”. In order to be able to manage crises effectively and it sets out a framework for the decision-making process should understand the steps of effective crisis management. The results of this paper indicate that the impact of the global crisis is being driven by the country’s high dependence on management of a financial crisis which led to regulation is rising and is creating new challenges that need managing. It is hoped that the study will be able to fill the gap in research in the area of crisis vision and change management regulation due to the limited literature on this area in emerging countries. Knowledge of effective crisis management policy is a significant in terms of providing an in-depth understanding of how decision-making can deal with crises. Further study in this area would be beneficial in helping management organisations to manage crises effectively.